2012
DOI: 10.1108/20420921211327365
|View full text |Cite
|
Sign up to set email alerts
|

The clinical profiles of forensic inpatients with intellectual disabilities in a specialized unit

Abstract: PurposeIndividuals with intellectual disability (ID), mental health needs and criminal justice system involvement are likely to be admitted to forensic units; however, not all of those individuals are served in that system. It is, therefore, important to understand the profile of those admitted to non‐forensic specialized units for individuals with ID and mental health issues. This paper aims to address this issue.Design/methodology/approachDemographic, clinical and criminal profiles of individuals discharged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…55,77,79,102,108 The remaining 15 papers reported data about in-patients with intellectual disability and/or autism in specialist intellectual disability services only (Table 3). 1,3,4,6,8,14,35,[73][74][75]78,104,[109][110][111] The mean and the average median length of stay within specialist in-patient intellectual disability services was longer compared with GMH inpatient services, but was shorter when those identified as long stay were removed (Table 4).…”
Section: Length Of Staymentioning
confidence: 99%
“…55,77,79,102,108 The remaining 15 papers reported data about in-patients with intellectual disability and/or autism in specialist intellectual disability services only (Table 3). 1,3,4,6,8,14,35,[73][74][75]78,104,[109][110][111] The mean and the average median length of stay within specialist in-patient intellectual disability services was longer compared with GMH inpatient services, but was shorter when those identified as long stay were removed (Table 4).…”
Section: Length Of Staymentioning
confidence: 99%
“…Participation in psychological interventions was already fairly well established in this forensic group due to a willingness to adapt existing mental health programmes and optimise treatment, yet the impact of such interventions is under‐reported. Other similar forensic services in Ontario, Canada have different challenges, in that they have forensic in‐patient psychiatry services, but no psychological services specific to in‐patients with ID (Palucka et al, 2012). Since the therapeutic emphasis in the programmes is targeted towards higher functioning individuals, it makes it difficult for people with ID to participate fully in treatment.…”
Section: Discussionmentioning
confidence: 99%
“…18 One of the few non-UK studies reported 'any criminal justice involvement', which included arrest without charge following discharge from an Australian hospital unit, arrest data being likely to be a better reflection of offending behaviour than conviction. 36 Only one linked series of studies attempted to address change in offending behaviour as a result of treatment, comparing the number of formal incidents in the 2 years before referral to a community FIDDs service with those in a follow-up period. 26,28,29 Five studies examined and attempted to measure 'offending-like' behaviour in the community that had not been officially recorded.…”
Section: Reoffending/'offending-like' Behaviour/incidentsmentioning
confidence: 99%